Research of influence technologies and methods of countering fishing - Мехед, Дмитро Борисович; Ткач, Юлія Миколаївна; Базилевич, Володимир Маркович (Ukrainian Information Security Research Journal, 2019)
An increasing number of information security attacks that have occurred in the last year could have been prevented. Digitalization continues to be one of the main trends in modern business, which entails the use of both proven and latest information technologies in all sectors. Information security experts around the world are continuously fighting cybercrime. This makes the attackers perfect their tools. At the beginning of last year, cyber attacks became a test for many organizations in various sectors of the economy. Many events in the field of information security could be prevented. The largescale and fast digitalization of all spheres of life and business that we are currently observing is based on the use of a mass of information technologies (both already proven and credible, as well as the latest). However, as practice shows, even security technologies that have been used for years have not been resolved. A cyber attack on a company with a well-organized defense system requires special knowledge and tools, as well as high financial and time costs. Multistage, carefully planned and organized cyber attacks aimed at a specific industry or specific, usually large, companies are called advanced persistent threats. The article analyzes the current threats to information security and makes a forecast of the main directions of cyber attacks in the future. Among the existing threats to information security, for several consecutive years, the leading position has been occupied by methods of social engineering. Cybercriminals continue to invent new methods of influencing users that would allow them to infect the target system with malware, steal money or gain access to confidential information. Phishing can take many forms and can be achieved using a variety of tools and techniques. During the analysis, the authors identified the most common tools and methods that are used to conduct phishing attacks. The analysis made it possible to formulate the necessary measures in order to reduce the number of successful phishing attacks. This is not an exhaustive list of possible actions, but a minimal set that will make it impossible to implement much of the social engineering toolkit.